Statistics and evaluation in the promotion of libraries - Heaney, Michel (2011)
I want to talk about the principles which support statistics and evaluation. We all undertake the collection and evaluation of statistics – you would not be here today if you were not interested in the work – but sometimes it is useful to stop and think about the reasons for doing it, and to put our activities into an overall context. I have used data published by the Libraries of UNLP to provide examples: Evaluación Objetiva De Las Bibliotecas De La UNLP Año 2006 and Encuesta De Calidad Del Servicio 2007 De Las Bibliotecas De La Universidad Nacional De La Plata.